(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Fractures of lower leg bones are a common type of injury, accounting for 18% of all bone fractures and are common in the working age group. Bone fixation technique with intramedullary nails has many advantages. At our hospital, surgical treatment of two lower leg bones fractures with intramedullary locking nails has been performed for many years. To evaluate the results of this treatment method, we conducted a reseach “The results of treatment of closed lower leg bones fractures with closed reduction, intramedullary locking nails at thong nhat dong nai general hospital”. Objectives: 1. General objective: To evaluate the results of closed lower leg bones fractures treatment with closed reduction and intramedullary locking nails under a brightening screen. 2. Specific goals: - To determine the rate of complications of surgical treatment with intramedullary nailing in the lower leg - Results of fracture reduction and rehabilitation - Relationship: Between results of fracture reduction and fracture severity; between results of rehabilitation and surgical time. Research method: Cross-sectional descriptive study Research results: We operated and followed up 35 cases. With very good results, there were 26 cases (74.3%), good cases in 09 cases (25.7%), and no average or bad results. There were no cases of complications, superficial post-operative infection accounted for 8.6%, no cases of deep infection or prolonged fistula inflammation. Conclusion: Superficial infection after surgery accounts for 8.6%, there are no cases of deep infection or prolonged fistula inflammation. Ages 18-60 account for the majority of 88.5%. Traffic accidents are the main cause of 82.6%. Closed fractures in the middle third are common, accounting for 71.4%, with type A fractures accounting for 85.7%, surgery time less than 60 minutes, approximately 88.5%, and very good recovery rate 74. .3%. Research results show that there is a relationship between fracture severity and fracture reduction results with Fisher’s exact index of 0.014. And there is also a relationship between the time of surgery and the results of rehabilitation with Fisher’s exact 0.0001.